Incorporating Conducting Polypyrrole into a Polyimide COF for Carbon‐Free Ultra‐High Energy Supercapacitor. Issue 34 (22nd July 2022) - Haldar, Sattwick; Rase, Deepak; Shekhar, Pragalbh; Jain, Chitvan; Vinod, Chathakudath Prabhakaran; Zhang, En; Shupletsov, Leonid; Kaskel, Stefan; Vaidhyanathan, Ramanathan
Abstract: Redox‐active covalent organic frameworks (COFs) store charges but possess inadequate electronic conductivity. Their capacitive action works by storing H + ions in an acidic electrolyte and is typically confined to a small voltage window (0–1 V). Increasing this window means higher energy and power density, but this risks COF stability. Advantageously, COF's large pores allow the storage of polarizable bulky ions under a wider voltage thus reaching higher energy density. Here, a COF–electrode–electrolyte system operating at a high voltage regime without any conducting carbon or redox active oxides is presented. Conducting polypyrrole (Ppy) chains are synthesized within a polyimide COF to gain electronic conductivity (≈10 000‐fold). A carbon‐free quasi‐solid‐state capacitor assembled using this composite showcases high pseudo‐capacitance (358 mF cm −2 @1 mA cm −2 ) in an aqueous gel electrolyte. The synergy among the redox‐active polyimide COF, polypyrrole and organic electrolytes allows a wide‐voltage window (0–2.5 V) leading to high energy (145 μ Wh cm −2 ) and power densities (4509 μ W cm −2 ). Amalgamating the polyimide‐COF and the polypyrrole as one material minimizes the charge and mass transport resistances. Computation and experiments reveal that even a partial translation of the modules/monomers intrinsic electronics to the COF imparts excellent electrochemical activity. The findings unveil COF‐confined polymers as carbon‐free energy storage materials. Abstract : Loading of polypyrrole into a polyimide covalent organic framework (COF) improves its electronic conductivity. The COF's carbonyl and imide functional groups interact with the cations, while the positively charged pyrrolic nitrogens store bulky anions. This enhances the overall voltage window of this carbon‐free capacitor device. The large pores of the COF are crucial in hosting bulky conducting polymers and electrolytes.